Positive regulation in the general amino acid control of Saccharomyces cerevisiae. - Hinnebusch, A G (1983)
Starvation of yeast for a single amino acid leads to derepression of enzymes in many different amino acid biosynthetic pathways. This general control is regulated by several transacting genes. Mutations in the TRA3 gene result in constitutive derepression, whereas mutations in AAS genes lead to the inability to derepress. We have isolated aas mutations as suppressors of the tra3-1 mutation. Some of these suppressors are alleles of AAS2 and others define a heretofore unidentified gene, AAS3. We have studied the regulatory behavior of strains containing both aas and tra3 mutations and strains containing the cloned AAS genes in high copy number. Either aas1- or aas2- in combination with tra3- has the Tra- phenotype, whereas aas3- in combination with tra3- has the Aas- phenotype. These interactions suggest that the AAS1 and AAS2 products act indirectly to bring about derepression by disabling the repressive effect of TRA3, whereas the AAS3 product functions more directly and is required even in the absence of the TRA3 function. When present in high copy number, the AAS3 gene complements mutations in AAS1 and AAS2, whereas AAS1 and AAS2 only complement their cognate mutations. Taken together these data suggest that AAS1 and AAS2 are negative regulators of TRA3, which in turn is a negative regulator of AAS3. AAS3 is a positive regulator, which is required for the general control response. This model of negative and positive interactions is formally identical to those proposed for the regulation of the galactose and phosphatase systems in yeast.